Glucose plus metformin compared with glucose alone on β-cell function in mouse pancreatic islets - HASHEMITABAR, MAHMOUD (Biomed Rep, 2015)
Metformin is currently the first drug of choice for treatment of type II diabetes. The primary function of metformin is to decrease hepatic glucose production mainly by inhibiting gluconeogenesis. The aim of the present study was to investigate the effects of glucose alone (control groups) and glucose and metformin (treatment groups) on pancreatic islets functions. Pancreatic islets were isolated by collagenase digestion and incubated for 24 or 48 h in RPMI-1640 containing 5 mmol/l glucose (control groups 1 and 2, respectively) or 24 h with 25 mmol/l glucose (control group 3) and 15 µmol/l metformin (treatment groups 1, 2 and 3, corresponding to the control groups, respectively). Subsequently, the rate of insulin output from islets, pancreatic and duodenal homeobox 1 (Pdx-1) and insulin genes expression and islet viability were assayed. The rate of insulin secretion in a 5 mmol/l glucose concentration in the 48 h treatment group increased significantly compared with that of the 24 h treatment group (P<0.05). An increase of the glucose concentration (25 mmol/l) caused insulin secretion to increase compared with that of 5 mmol/l glucose. Pdx-1 gene expression in treatment group 2 significantly decreased compared with the control group 2 (P<0.05). The the Pdx-1 gene expression in treatment group 2 decreased compared with that of the treatment group 1. The expression of the insulin gene in treatment group 1 increased compared with control group 1, and in treatment group 2, there was a 2-fold increase in insulin gene expression compared with control group 2. The insulin gene expression in treatment group 2 increased compared with treatment group 1. The percentage of islet cell viability was increased in treatment group 3 by ~40% compared with the islet cells of treatment groups 1 and 2 (P<0/05). These data indicate that glucose and metformin have direct effects on β-cell function.